Communication Ethics In Using Social Media From Hadith Perspective - Andi Ahmad Zahri Nafis; Zulfahmi Alwi; Arifuddin Ahmad; Nirwan Wahyudi; M. Napis Djuaeni (Jurnal Khabar: Komunikasi dan Penyiaran Islam, 2025)
This study examines the ethics of communication on social media through the perspective of hadith as a response to crucial issues in contemporary discourse. The main goal is to identify and analyze the ethical principles of digital communication based on the guidance of the Prophet PBUH. The method used is qualitative based on library research with a thematic analysis approach (maudhu'i), which includes sanad criticism, matan criticism, and hermeneutic analysis of related hadiths. The results of the study formulated four main principles in communicating in cyberspace. First, the message delivery must be positive by prioritizing good words and avoiding unhelpful content. Second, honesty in communication is the main foundation to prevent the spread of hoaxes that often trigger social conflicts. Third, it is important to consider the impact of each message to be delivered (the aspect of maslahat), considering that every speech has moral and spiritual consequences. Fourth, it is necessary to avoid messages that contain insults, hatred, and sheep fighting, which are in harmony with the hadith commands to protect the mouth and heart from envy and envy. This study concludes that the ethical values in the hadith of the Prophet Muhammad PBUH remain very relevant as a universal moral guideline for social media users to create a healthy, harmonious, and responsible digital environment.